Urgensi Pendidikan Anak Berkebutuhuan Khusus dalam Surah Abasa Ayat 1-10 dalam Tafsir Ibnu Katsir: Nilai-nilai Pendidikan Anak Berkebutuhan Khusus dalam surat Abasa ayat 1-10 - Oky Abdul Rohman; Bustanul Ulum, M. (Kartika: Jurnal Studi Keislaman, 2025)
This study explores the urgency of education for children with special needs (CSN) in light of Surah ‘Abasa (1-10) through Ibn Kathir’s exegesis. Using a qualitative library research method, the study analyzes classical and contemporary tafsir literature relevant to inclusive education. The findings highlight that Surah ‘Abasa conveys a fundamental message of equality in educational access. Allah’s admonition to the Prophet ﷺ regarding Abdullah ibn Umm Maktum, a blind companion, affirms that the right to education must not be restricted by physical limitations or social status. The analysis identifies four core values essential to inclusive education: equality, compassion, appreciation of potential, and inclusiveness. These values provide theological legitimacy for inclusive education in Islam while connecting classical exegesis with modern educational theory. The study contributes theoretically by enriching Islamic educational discourse, practically by guiding institutions to design inclusive learning, and at the policy level by supporting the implementation of inclusive education regulations in Indonesia. Future research should extend the discussion by examining other exegetical works, such as those of Al-Qurtubi and At-Tabari, and by conducting field studies in pesantren-based inclusive schools. This research thus strengthens the paradigm of Islamic education that is humanistic, inclusive, and just.